Precipitated Calcium Carbonate Derived from Green Mussel Shells Extracted from Magnesium Chloride Containing Solution. Issue 1 (1st October 2022) - Irfa'i, M.A.; Prihanto, A.; Muryanto, S.; Jamari, J.; Ismail, R.; Bayuseno, A.P.
Abstract: Green mussel shells are one of the calcium carbonate-rich biogenic sources. They contain 95.7 to 98.2 wt. % calcium. The high calcium content of green mussel shells was extracted and converted into calcium oxide material in the study by calcination at 900°C for 5 h. Later, at stirring times of 30, 60, 90, and 120 minutes, a solution medium containing magnesium chloride was used to dissolve the resulting calcination powder and subsequent carbonation for producing PCC (precipitated calcium carbonate). According to XRD, Rietveld, and FTIR analyses, the resulting PCC product with calcite-containing Mg was obtained primarily for a short stirring time of 30 minutes during the carbonation process, whereas calcite and aragonite were generated at longer stirring times (from 60 to 90 minutes). Instead, brucite was obtained after 120 minutes of stirring. The PCC product has a non-uniform polyhedrallic morphology of various small and large sizes as observed by SEM. This powder processing method allowed for faster PCC synthesis at a lower cost while requiring no chemical addition to increase basicity.